EKSTRAKSI KATA KUNCI OTOMATIS UNTUK DOKUMEN BAHASA INDONESIA STUDI KASUS: ARTIKEL JURNAL ILMIAH KOLEKSI PDII LIPI - Sari, Diana; Purwarianti, Ayu (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2014)
Keyword determination by using controlled vocabulary is not a difficult task for information analysts. However,specify keywords for hundreds or even thousands of articles will take time and effort of the analysts. To ease thework, it needs to be made a system of automatic keyword extraction. The construction of this system passes thestages of preprocessing, translating, and pinpointing keyword candidates with a list of keywords. The research wascarried out by using 33 articles taken from PDII LIPI journal collections. This research employed 3 weighing methods,namely TF, TF x IDF and WIDF. The best result was obtained from TF x IDF method. To refine the result, the authorcarried out fixing the keywords results and using levensthein algorithm.